A closer look at response options: Is judgment in situational judgment tests a function of the desirability of response options?. (13th March 2019) - Kaminski, Katarina; Felfe, Jörg; Schäpers, Philipp; Krumm, Stefan
Abstract: The current study builds on the current scholarly debate about SJTs potentially being less situational than previously assumed. Specifically, we respond to recent calls to examine general (situation unspecific) information included in response options as a guide to SJT responses. Across three consecutive studies and three different forms of SJT administration (standard, without situation descriptions, under fake‐good instructions), the relevance of social desirability of response options on SJT responses was examined. Results suggest that social desirability of response options is significantly related to test takers' response. This finding generalized across different forms of SJT administration. Across studies and together with the plausibility of response options, desirability explained about one‐third of reliable variance in test takers' response to an SJT. Implications for SJT theory and development are discussed.